Materials design and modification on amide-based composites for hydrogen storage - Cao, Hujun; Zhang, Yao; Wang, Jianhui; Xiong, Zhitao; Wu, Guotao; Chen, Ping (Progress in natural science, 2012)
<正>Amide-based composite system has the potential to meet the needs of onboard hydrogen storage for fuel cell vehicles due to its relatively high hydrogen capacity and tunable thermodynamics. A large number of amide-hydride and amide-complex hydride composites have been developed in the past decades.This article reviews the state-of-the-arts of amide-hydride composite systems with the focus on the materials design and modification.